Policy dialogue between multilateral institutions and developing countries - Otto G. Mayer (Intereconomics, 1990)
The lending criteria applied by the IMF and the World Bank have been converging for some time. Considering also that since the floating of exchange rates in the early seventies the IMF seems to have lost in importance as a monetary institution, debate is growing on the question of whether the Fund needs to correct its policy course, to be assigned new tasks by its member countries or even to be amalgamated with the World Bank into one efficient development aid institution.
Keywords: 330; Bretton Woods Institutions